2004
DOI: 10.1093/ije/dyg267
|View full text |Cite
|
Sign up to set email alerts
|

Atopic dermatitis and the hygiene hypothesis: a case-control study

Abstract: Increased exposure to infection does not explain the reduced risk of AD in second and subsequent siblings. More generally, these data cast doubt on the hygiene hypothesis as a causal explanation for AD in young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(12 citation statements)
references
References 48 publications
2
9
0
1
Order By: Relevance
“…Our EBV incidence estimates are comparable to results from previous UK studies [3638]. Differences in paediatric EBV prevalence by ethnic group have been reported from two US studies [22, 39] and one in the Netherlands [32].…”
Section: Discussionsupporting
confidence: 89%
“…Our EBV incidence estimates are comparable to results from previous UK studies [3638]. Differences in paediatric EBV prevalence by ethnic group have been reported from two US studies [22, 39] and one in the Netherlands [32].…”
Section: Discussionsupporting
confidence: 89%
“…Karmaus et al [16 ]found this effect to be strongest among atopic mothers. Gibbs et al [17 ]reported in a case control study that increased exposure to infection did not protect children from atopic dermatitis, in spite of a strong birth order effect.…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations to this phenomenon are attributing to the level of stress and the difference in abiotic factors such as air and water and life span or health of people. Most importantly, distribution of helpful microorganisms is mainly derived from the types of foods consumed (19,20). The potential roles of microbiome on diverse disorders are summarized below.…”
Section: Introductionmentioning
confidence: 99%